2003
DOI: 10.1021/bi034879h
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Bovine Insulin Probed by DSC/PPC Calorimetry and FTIR Spectroscopy

Abstract: Pressure perturbation calorimetry (PPC), differential scanning calorimetry (DSC), and time-resolved Fourier transform infrared spectroscopy (FTIR) have been employed to investigate aggregation of bovine insulin at pH 1.9. The aggregation process exhibits two distinguished phases. In the first phase, an intermediate molten globule-like conformational state is transiently formed, reflected by loose tertiary contacts and a robust H/D-exchange. This is followed by unfolding of the native secondary structure. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
191
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 41 publications
21
191
0
1
Order By: Relevance
“…2b (black line) yields a DNA ejection enthalpy of 2 ϫ 10 Ϫ16 J/virion, which is in precise agreement with the value we previously obtained by ITC for receptor-triggered DNA ejection (26). The peak position and resulting enthalpy per virion are independent of virus concentration in the DSC scans, suggesting that nonspecific intermolecular reactions such as protein aggregation (which can create artificial exothermic heats [34]) do not contribute to this peak. Although our focus is on the process of DNA release from virions, it is interesting to note the effect of EDTA addition on thermal stability of the constituent parts of the virus-the protein capsid and dsDNA genome.…”
Section: Mgsupporting
confidence: 87%
“…2b (black line) yields a DNA ejection enthalpy of 2 ϫ 10 Ϫ16 J/virion, which is in precise agreement with the value we previously obtained by ITC for receptor-triggered DNA ejection (26). The peak position and resulting enthalpy per virion are independent of virus concentration in the DSC scans, suggesting that nonspecific intermolecular reactions such as protein aggregation (which can create artificial exothermic heats [34]) do not contribute to this peak. Although our focus is on the process of DNA release from virions, it is interesting to note the effect of EDTA addition on thermal stability of the constituent parts of the virus-the protein capsid and dsDNA genome.…”
Section: Mgsupporting
confidence: 87%
“…This topic is a challenge for the understanding of amyloidoses which are a variety of diseases or pathological states that share the common property of b-structured protein fibril deposits (amyloids). High-pressure experiments have been performed using both model and pathological proteins (47)(48)(49)(50)(51). As pointed out recently by Foguel and Silva (52): "The use of high pressure promises to contribute to the identification of the mechanism behind these effects and the creation of therapies against these diseases".…”
Section: Role Of the Partial Molar Volume Of Proteins The Case Of Anmentioning
confidence: 99%
“…The thermodynamic data on the stability of amyloid fibrils obtained by DSC (Morel et al 2010) and ITC (Kardos et al 2004) indicate the contribution of entropy increase attained with their assembly, which points toward hydration effects playing a major role in this process. Previous DSC studies have also shown that thermalinduced aggregation of several proteins is accompanied by the exothermic effect of heat (Dzwolak et al 2003;Stirpe et al 2008;Attanasio et al 2009;Murciano-Calles et al 2010). Such an effect may be explained by a nucleation model, i.e., the formation of a stable nucleus that incorporates additional monomeric proteins into a growing aggregate (Dzwolak et al 2003), but the exact molecular basis remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Previous DSC studies have also shown that thermalinduced aggregation of several proteins is accompanied by the exothermic effect of heat (Dzwolak et al 2003;Stirpe et al 2008;Attanasio et al 2009;Murciano-Calles et al 2010). Such an effect may be explained by a nucleation model, i.e., the formation of a stable nucleus that incorporates additional monomeric proteins into a growing aggregate (Dzwolak et al 2003), but the exact molecular basis remains elusive. Recently, Goto and colleagues closely studied the thermal behaviors of amyloid fibrils formed from β 2 -m using DSC (Sasahara et al 2005(Sasahara et al , 2006(Sasahara et al , 2007a(Sasahara et al , b, 2009.…”
Section: Introductionmentioning
confidence: 99%